Physiotherapy student’s perception of problem based learning - Dhumale, Supriya (International Journal of Research in Medical Sciences, 2020)
Background: Problem based learning ensures that students are actively engaged in their learning- they set their own objectives and they reinforce what they have learned through discussion with their colleagues. This approach is known to promote deep learning, in contrast to much of the superficial learning happens in traditional methods. To support their learning through engaging them in learning activities and providing feedback. Student’s ability to perform in a professional context, to recognize their need to acquire new knowledge and skills and to view learning holistically. Objective of the study was to assess the third year physiotherapy students’ perception of problem based learning sessions in musculoskeletal condition. Methods: The study was conducted on 22 students of III-year physiotherapy graduate course. Sequential arrangement of PBL sessions was implemented by triple jump assessment on osteoarthritis of knee. Post project feedback questionnaire from students obtained from self-assessment, peer assessment. The responses obtained were analyzed. Results: All the student strongly agreed that The PBL scenarios motivated them to use additional learning resources, The PBL scenarios stimulated their interest in musculoskeletal. The students also agreed that the content of the PBL scenarios fitted their level of knowledge; The PBL scenarios effectively illustrated medical concepts. All the students totally agreed that PBL sessions appeared able to assess their own strengths and weaknesses within PBL, accepted and responded to criticism gracefully. Their peers gave input which was focused and relevant to the case, they were able to communicate well with each other. Students agreed that everyone among group completed tasks on time, they were actively participated in session, they shared new relevant information with group hence they felt their peers were responsible and respected. Conclusions: Students felt that the cases effectively illustrated medical concepts and fitted and reinforced the student musculoskeletal knowledge. They were convinced that scenarios motivated them to use additional resources and stimulated their interest and they enjoyed the process.